Analysis on network scheme and resolution test of SDN/NFV technology co-deployed in cloud datacenter - Rong GU; Ruixue WANG; Chen LI; Lu HUANG (Dianxin kexue)
Traditional datacenters have been heavily impacted due to the development and large-scale deployment of cloud computing technology.Co-deployment of SDN and NFV technology shows its distinct advantages of vitualizing network resources in the scenario of cloud datacenter.Resolution tests aiming at co-deployment of SDN and NFV have directive significance.According to the resolution test,SDN and NFV technology were matured already for the commercial deployment in operators' network.Further research needs to be focused on the key problems found out in scheme designing and the resolution test.